1981
DOI: 10.1021/bi00517a022
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the nature of enzyme-coenzyme interactions in binary and ternary complexes of liver alcohol dehydrogenase with coenzymes, coenzyme analogs, and substrate analogs by ultraviolet absorption and phosphorescence spectroscopy

Abstract: The difference spectra of binary and ternary complexes of horse liver alcohol dehydrogenase with oxidized and reduced nicotinamide adenine dinucleotides, nicotinamide 1,N6-ethenoadenine dinucleotide, and adenosine diphosphate ribose along with a number of substrate analogues have been measured. These spectra bear a very close resemblance to those obtained by perturbation of the coenzyme(s) and their analogues by acid, NaCl, dioxane, or tert-butyl alcohol. It is inferred that the coenzymes experience a combinat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 27 publications
1
20
0
Order By: Relevance
“…Furthermore, combining the enthalpy with entropy changes, interactions between HCPT and Ce6 molecules were mainly hydrophobic interaction (Δ H 1 >0, Δ S 1 >0; Δ H 3 >0, Δ S 3 >0) and electrostatic attraction (Δ H 2 <0, Δ S 2 >0). So it was confirmed that the assembly mechanism of the NRs was mainly the hydrophobic interaction (the π–π conjugation of the ring structure) and the electrostatic interaction between HCPT and Ce6 molecules 35,36. The association constant (n=3) indicated that one molecule of Ce6 probably combined with three HCPT molecules.…”
Section: Resultsmentioning
confidence: 78%
“…Furthermore, combining the enthalpy with entropy changes, interactions between HCPT and Ce6 molecules were mainly hydrophobic interaction (Δ H 1 >0, Δ S 1 >0; Δ H 3 >0, Δ S 3 >0) and electrostatic attraction (Δ H 2 <0, Δ S 2 >0). So it was confirmed that the assembly mechanism of the NRs was mainly the hydrophobic interaction (the π–π conjugation of the ring structure) and the electrostatic interaction between HCPT and Ce6 molecules 35,36. The association constant (n=3) indicated that one molecule of Ce6 probably combined with three HCPT molecules.…”
Section: Resultsmentioning
confidence: 78%
“…The mechanism for the quenching of the tryptophan fluorescence of ADH that results from formation of binary and ternary complexes has been the subject of controversy (Laws and Shore, 1978;Laws and Shore. 1979;Subramanian et al, 1981;Eftink, 1986). In the case of the pyrazole ternary complex with NAD + , singlet-singlet resonance energy transfer has been proposed as the mechanism for the preferential quenching of Trp-314 .…”
Section: Discussionmentioning
confidence: 99%
“…Triplet state investigations of pyridine nucleotide dependent enzymes have been limited to the aromatic amino acids. tyrosine and tryptophan (Purkey and Galley, 1970;von Schiitz et al, 1974;Subramanian et al, 1981). The pyridine nucleotide coenzymes are themselves potentially useful triplet state probes, and it is of interest that their triplet state characteristics complement their singlet state properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This can also be done in the presence of tryp-tophan because the phosphorescence spectra of tyrosinate and tryptophan are well resolved. (202) By contrast, phosphorescence or fluorescence resulting from excited-state ionization will have an excitation spectrum characteristic of tyrosine. Moreover, the decay kinetics of the product formed in the excited state will have a characteristic signature, specifically a kinetic component with a negative amplitude, (26) and short lifetime in the case of tyrosinate.…”
Section: Fluorescence Of Tyrosinatementioning
confidence: 99%